Pro SQL Server Disaster Recovery - Luetkehoelter, James; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2008)
Many would argue that the single most important job of a SQL Server database administrator is to be able to recover your database in the event of loss or damage. Pro SQL Server Disaster Recovery helps you meet that goal by showing you how to think about and plan for potential problems. You'll learn to anticipate and reduce the likelihood of a disaster, and to mitigate the effects of a disaster when one does occur. Perhaps most importantly, you'll learn how to prepare so that you can return a system to its normal state quickly, ensuring system availability and the continued success and operation of your business. Many SQL Server features and technologies are, or can be put to good use in disaster recovery planning. In this book, you'll learn about powerful tools and features—such as Database Snapshots and Mirroring—for data backup and disaster recovery that are present in SQL Server 2005, and that are enhanced in SQL Server 2008. Also covered are common issues to expect when using these features. This book explores your options by examining the technical details of disaster recovery features and then applying that knowledge to practical scenarios. There's a human side to disaster recovery planning as well. Like few other activities, disaster recovery planning requires that you work closely with a wide variety of people from all across your organization. People skills are as critical to disaster recovery planning as technical skills, and perhaps more so. This book does not leave you in the dark, but provides sound advice on how to keep disaster recovery planning projects on track, how to avoid dangerous scope creep, and how to work effectively with the variety of personality types that you will encounter. Disaster recovery planning is really about sleep. When you get the call at 3:00 am that your database is lost, don't wake up with that icy feeling in your veins. Instead, wake up with confidence that you have a plan in place, a plan that you've practiced, that management has bought into, a plan that you can execute even while half–asleep to get your database, your company, and your job back on track.
What Is Disaster Recovery? -- Making Database Backups -- Restoring a Database -- Backing Up and Restoring Files and Filegroups -- Creating a Backup/Recovery Plan -- Maintaining a Warm Standby Server via Log Shipping -- Clustering -- Database Mirroring -- Database Snapshots -- Hardware Considerations -- Disaster Recovery Planning -- Realistic Disaster Recovery Planning.
Keywords: Database management; Software engineering; Database Management; Software Engineering/Programming and Operating Systems